Study guides

Q: 2 divided y plus 1 plus 3 divided 5y?

Write your answer...

Submit

Related questions

X = 17.7 + 0.1y

2y^2+5y+2=(2y+1)(y+2)

(4y - 1)(5y + 2)

The multiplicative inverse of 5y -xy + 1 is 1/5y -xy + 1 The additive inverse of 5y - xy + 1 is -5y + xy - 1

(5y - 1)(5y - 1) or (5y - 1)2

(2, 1)

(1, -1)

5y + 7 = 25y = -5y = -1

5y-2y= 3y+2 5y-2y-3y= 2 0y= 2

6x

6x

Yes, since the expression contains more than one variable, then 2x+5y+2 is a polynomial.

3 divided by 4 plus 1 divided by 2 minus 2 divided by 3

(-5, 2)

(-1, 2)

x + 5y = 10 5y = -x + 10 y = -x/5 + 2 m = -1/5 or .2

5y + 1 = 4y - 1 Subtract 4y from both sides of the equation. y + 1 = -1. Add 1 to both sides of the equation. y + 2 = 0 Subtract 2 from both sides of the equation. y = -2

7

The answer is 2.

3x + 5y = -1 2x - 5y = 16 Add the two equations: 5x = 15 or x = 3 Substitute for x in the first equation: 3*3 + 5y = -1 15 + 5y = -1 5y = -10 so y = -10/5 = -2 The solution is (x, y) = (3, -2)

ANSWER:1+1= 2/1=2+1=3/1=3+1=4/1=4+1=5/1=5+1=6the answer is 6answer is 2.If you put parentheses after all your "divided by" 's and go on forever, this converges to the golden ratio.

2 plus 1-x divided by.

the answer is -0.126875

22 + y

(x, y) = (3, 2)